Dampak Pemilu Terhadap Pertumbuhan Kredit Perbankan - Aryanti Sariartha, Alfiana & Vicentia Wahju Widajatun (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2015)
This study examines the impact of political event specifically political elections on credit growth in banking industry. This study conducted in a period of December 2007 through November 2012. We studied all banks operated in Indonesia. Using dummy variable to measure the impact of elections, this study found that elections affect the behaviour of banking industry specifically on issuing credits. Time series data showed evidence that banks distributed higher credits two months prior the election, in a period of election, and two months after election. Our findings consistent when we employed probit regression of economic indicators, capital market index (IHSG), inflation, and foreign exchange to generate measures of elections. Findings also consistent with several control variables such as capital adequacy ratio, liquidity ratio, contagion, and bank run. This research generate conclusion that elections brought positive impact on loan growth of banking industry, consistent with prior studies predicted bank behavior of delivering credits in political elections.